Advances in early diagnosis and treatment of Crohn's disease - Liang CHEN; Chun-Jin XU; Zhan-Ju LIU (Yixue xinzhi zazhi)
The early symptoms of Crohn's disease (CD) are atypical and lacking in specificity so ren-dering early diagnosis of CD challenging. Therefore, improving the identification of early CD is conducive to early diagnosis and timely treatment, thus improving the prognosis of patients with CD and reducing the disability rate and associated disease burden. This paper reviews the research progress in develop-ing early diagnostic biomarkers and targeted biotherapy for CD.